Smart Mobility dan Pembangunan Berkelanjutan: Analisis Potensi Kota Cerdas di Sumatera Utara - Harahap, Hastuti Handayani; Rajagukguk, Frederick Rudy Sentosa; Arifin, Indra Welly (Digital Business Progress, 2025)
Urban development in North Sumatra Province has experienced significant population mobility growth, yet it still faces challenges such as traffic congestion, air pollution, and limited public transportation. This study aims to analyze the potential implementation of the smart mobility concept to support sustainable development and the transformation toward smart cities in North Sumatra. The research employs a qualitative approach using literature review and descriptive analysis to identify urban mobility conditions, challenges, as well as the inhibiting and supporting factors for smart mobility implementation. The results indicate that smart mobility can enhance transportation efficiency, reduce carbon emissions, and improve public service quality. Key supporting factors include government commitment, the growth of the digital ecosystem, and public awareness of green transportation, while inhibiting factors include infrastructure limitations, weak cross-sector coordination, and funding constraints. This study recommends an integrative strategy involving digital infrastructure development, sustainable transportation policies, multi-stakeholder collaboration, and public education to achieve effective and sustainable smart mobility.